Visual art education teacher’s beliefs and attitudes toward incorporating ICT into art classrooms / Mohd Khairezan Rahmat and Wing K. Au. - Rahmat, Mohd Khairezan; Wing, K. Au (2018)
Visual art is a subject that emphasizes on creativity, innovation and critical thinking, therefore, Visual Art Education (VAE) teachers have been urged to utilize the full potential of Information and Communication Technology (ICT). Despite numerous literatures have highlighted the benefits of ICT, VAE teachers were found not serious toward integrating ICT in teaching. Hence, this study was carried out to determined Malaysian VAE teachers’ attitudes and beliefs and their level of confidence toward incorporating ICT into art classrooms. This study explored teachers’ specific approach of ICT and factors that influence their integration of ICT into art classrooms. The participants of this study were eighteen VAE teachers from three-selected secondary school in the state of Selangor, Malaysia. Data for the study was gathered by face-to-face interviews. The findings of the study indicated that Malaysian VAE teachers were still at moderate levels of ICT integration. The support from school administrator and continues professional development were identified as two main factors that contribute towards successful ICT integration. In light of the published research on the integration of ICT in the VAE subject area, hopefully, the findings of this study will assist school organization, teachers training institutions and the Ministry of Education toward establishing a standard for successful ICT integration, especially in the context of the VAE.